Analisis Pengaruh Komitmen Organisasional dan Kepuasan Kerja Terhadap Turnover Intention Karyawan PT. Sayap Emas Gemilang - Widy Taurus Sandy; Erik Bisri Alamsyah (Fakultas Ekonomi Universitas Yos Soedarso, 2024)
This research aims to examine the impact of Job Satisfaction and Organizational Commitment on the Turnover Intention of production employees at PT. Sayap Emas Gemilang. The method used in this study is explanatory, with data collection conducted directly in the field. The population and sample involve all employees at PT. Sayap Emas Gemilang, totaling 43 individuals. Data analysis was performed using Multiple Linear Regression, Hypothesis Testing, and the Coefficient of Determination. The findings indicate a significant negative effect of Job Satisfaction on Turnover Intention at PT. Sayap Emas Gemilang; meaning, the lower the job satisfaction, the higher the Turnover Intention. Furthermore, Organizational Commitment also has a significant negative impact on Turnover Intention, where a decrease in Organizational Commitment increases the level of Turnover Intention among employees.